2017
DOI: 10.1136/bmjopen-2017-016487
|View full text |Cite
|
Sign up to set email alerts
|

A study protocol for a multicentre randomised clinical trial evaluating the safety and feasibility of a bioengineered human allogeneic nanostructured anterior cornea in patients with advanced corneal trophic ulcers refractory to conventional treatment

Abstract: IntroductionThere is a need to find alternatives to the use of human donor corneas in transplants because of the limited availability of donor organs, the incidence of graft complications, as well as the inability to successfully perform corneal transplant in patients presenting limbal deficiency, neo-vascularized or thin corneas, etc. We have designed a clinical trial to test a nanostructured fibrin-agarose corneal substitute combining allogeneic cells that mimics the anterior human native cornea in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 31 publications
0
21
0
1
Order By: Relevance
“…In a first clinical case, the compressed collagen matrix was used to fill the ulcerated defect region (as a corneal inlay) while a second identical matrix was used to cover the cornea as a bandage (onlay). 56 While the bandage onlay degraded within the first postoperative week, it facilitated coverage of the entire ulcerated region by recipient corneal epithelium, with the inlay portion remaining intact. During the following six month period, the inlay also degraded but with epithelium remaining intact without signs of inflammation or immune rejection.…”
Section: Bioengineered Acellular Corneal Stromamentioning
confidence: 99%
“…In a first clinical case, the compressed collagen matrix was used to fill the ulcerated defect region (as a corneal inlay) while a second identical matrix was used to cover the cornea as a bandage (onlay). 56 While the bandage onlay degraded within the first postoperative week, it facilitated coverage of the entire ulcerated region by recipient corneal epithelium, with the inlay portion remaining intact. During the following six month period, the inlay also degraded but with epithelium remaining intact without signs of inflammation or immune rejection.…”
Section: Bioengineered Acellular Corneal Stromamentioning
confidence: 99%
“…However, one of the limitations of the present study is the need of performing all quality control analyses required by national Medicines Agencies for clinical translation of advanced therapies medicinal products generated by tissue engineering, including biomechanical, biodegradation, porosity, vascularization, and biocompatibility characterization once grafted in vivo. The fact that the basic biomaterial used in the present work fulfilled all these requirements and is currently approved for clinical use [22,23] supports the future clinical usefulness of F-FAOM, but future in vivo analyses should determine the real potential of these novel functionalized tissues. Another limitation is the lack of long-term follow-up, as tissues were analyzed up to 3 weeks.…”
Section: Discussionmentioning
confidence: 64%
“…From a technical standpoint, we found that novel F-FAOM could be easily generated in the laboratory by combining small oral mucosa biopsies with fibrin-agarose biomaterials previously used in tissue engineering [17,18,20], without the need of establishing primary cell cultures previously. Nonfunctionalized fibrin-agarose biomaterials have previously shown adequate biomechanical properties [16] and very good in vivo biocompatibility in animal models [13,21], which allowed us to use these biomaterials in patients [22,23] with promising preliminary results. However, it is well known that previous non-functionalized bioartificial periodontal tissue models typically require several weeks of culture to obtain adequate numbers of stromal cells, followed by a maturation time of the bioartificial tissue of ~3 weeks once the tissue construct is generated [5].…”
Section: Discussionmentioning
confidence: 99%
“…En los últimos años, el hidrogel de fibrina-agarosa se ha utilizado con éxito para generar modelos similares a tejidos con bioingeniería para aplicaciones clínicas (27)(28)(29). Después de estudios ex vivo y en estudios vivo-preclínicos, los modelos basados en fibrina agarosa de córnea y piel se elaboraron como productos médicos avanzados en condiciones GMP(Good manufacturing practices) para uso clínico (30). Estudios recientes demostraron la posibilidad de mejorar las propiedades estructurales, biomecánicas y biológicas de la fibrina agarosa mediante el uso de la técnica de nano-estructuración, el uso de agentes reticulantes químicos o la combinación de ambos (31,32).…”
Section: Discussionunclassified